Anatomical pathology department of Siberian State Medical University. Toroptsev I.V. (1907—1985) to 95th jubilee - O. M. Ordina; G. V. Borisova; Yu. M. Paderov; V. V. Nedosekov (Бюллетень сибирской медицины, 2002)
Biography of the great scientist-pathologist, professor of Tomsk medical institute (Siberian State Medical University at present) I.V. Toroptsev — one of the founders of radio- and magnetobiology.